Improving Thermoeconomic and Environmental Performance of District Heating via Demand Pooling and Upscaling - Jaume Fitó; Neha Dimri; Julien Ramousse (Energies, 2021)
This study evaluates the effects of pooling heat demands in a district for the purpose of upscaling heat production units by means of energy, exergy, economic, exergoeconomic, and environmental indicators, as well as the sensitivity to investment and fuel costs. The following production systems to satisfy the heat demands (domestic hot water production and space heating) of a mixed district composed of office (80%), residential (15%), and commercial (5%) buildings are considered: gas- and biomass-fired boilers, electric boilers and heat pumps (grid-powered or photovoltaic -powered), and solar thermal collectors. For comparison, three system sizing approaches are examined: at building scale, at sector scale (residential, office, and commerce), or at district scale. For the configurations studied, the upscaling benefits were up to 5% higher efficiency (energy and exergy), there was lower levelized cost of heat for all systems (between 20% and 54%), up to 55% lower exergy destruction costs, and up to 5% greater CO2 mitigations. In conclusion, upscaling and demand pooling tend to improve specific efficiencies, reduce specific costs, reduce total investment through the peak power sizing method, and mitigate temporal mismatch in solar-driven systems. Possible drawbacks are additional heat losses due to the distribution network and reduced performance in heat pumps due to the higher temperatures required. Nevertheless, the advantages outweigh the drawbacks in most cases.